Strategi Peningkatan Literasi Sains dan Matematika Siswa SD - Kartikasari .; Carlista Mega Septiani; Annisa Noviarani; Puji Darwis; Rina Hidayati Pratiwi (CV. ITTC INDONESIA, 2025)
Elementary school students' science and mathematics literacy remains relatively low. According to the 2022 PISA literacy score, Indonesia lags behind the global average. In 2015, Indonesia ranked 44th out of 49 countries. The purpose of this study was to determine strategies for improving elementary school students' science and mathematics literacy. This research method used a Systematic Literature Review (SRL) to analyze literature from various relevant sources. Data collection was conducted through articles and scientific works from the last five years (2020-2025) obtained through the Sinta-indexed Google Scholar database. The study concluded that the factors causing low elementary school students' science and mathematics literacy are student misconceptions, an unsupportive learning environment, low reading interest, conventional learning techniques, and limited school facilities and infrastructure. Effective strategies used are the School Literacy Movement (GLS), the use of digital technology platforms, interactive media such as Interactive Flat Panel Displays (IFDP), and creative learning methods.